Pancasila as the Single Principle: Its Urgency for the Importance of Indonesian Muslims (Journal of Namibian Studies : History Politics Culture, 2023)
This paper aims to explore and explain the urgency of the Single Principle of Pancasila for the benefit of Indonesian Muslims. This writing was inspired by President Soeharto's speech in front of the session of the House of Representatives of the Republic of Indonesia on August 16, 1982, which raised, among other things, the urgency of the Single Principle of Pancasila for the national unity and integrity. However, this, later, received strong protests, especially from Muslims, because it was considered that it would make Pancasila a religion. In fact, the main mission of the Single Principle of Pancasila is to solve the basis issue of the community organizations before the state of Indonesia was passed on to the Post-45 generations. Using a historical-socio-political approach, it can be seen that behind the acceptance of Pancasila as the only principle by Muslims there is a great wisdom, namely the loss of concern or suspicion that Muslims have not fully accepted a national state based on Pancasila. With this loss of suspicion, the interests of Muslims are getting more attention from the state, among them are: (1) religious teachings are increasingly permittable, even supported; (2) the aspirations of Muslims one after another are fulfilled, such as the enactment of the Religious Justice Act, the National Education System Act, the Compilation of Islamic Law, the broadcasting of Arabic lessons on television; (3) religious life is becoming more vibrant; and (4) Islamic studies are also developing. However, when there was a reform, the policy of enforcing the Single Principle of Pancasila was actually revoked with the issuance of the Decree of the People's Consultative Assembly Number: XVIII / MPR / 1998 of 1998, thus opening up opportunities for riots and divisions of the nation.